Outcomes of Staphylococcal Prosthetic Joint Infection After Hip Hemiarthroplasty: Single Center Retrospective Study - Ahmed Nageeb Mahmoud; Nicholas R. Brule; Michael Suk; Daniel Scott Horwitz (Medicina)
Background and Objectives: When prosthetic joint infections, known for their high morbidity, are caused by high-virulence organisms such as Staphylococcus, the outcomes are even worse. This study aims to examine the outcomes of staphylococcal prosthetic joint infections after hemiarthroplasty for hip trauma patients, which has not been particularly reported. Materials and Methods: A retrospective study was performed in a level 1 trauma center to review all the cases of prosthetic joint infections in our database. Patients’ demographics, clinical inpatient, surgical, and outpatient notes, laboratory results, and serial radiographs were assessed to extract all relevant data. Results: Out of 2477 hip hemiarthroplasty cases reviewed, a total of 36 prosthetic joint infection cases caused by Staphylococcus species in 36 patients were included in this study. Patients were 26 females and 10 males with a mean age of 76.5 years at the time of surgery. Fifteen cases had infections with methicillin-resistant Staphylococcus aureus (MRSA) while twenty-one cases had infections with other Staphylococcus species. The mean follow-up for all cases is 43.5 months. Twenty-nine cases underwent at least a single trial for surgical debridement and implant retention surgery, and only nine (31%) had successful debridement and implant retention. The 3-month, 1-year, and 3-year cumulative mortality for all cases was 22.2, 30.5, and 41.7%, respectively. Conclusions: Staphylococcal hemiarthroplasty infection is a devastating complication that is associated with a low success (31%) of implant retention surgery, significantly high morbidity, and high cumulative mortality.